Implikasi RUU-BHP dan Perpres 77/2000 - Sofian Effendi (Universitas Islam Indonesia, 2008)
Essentially, national education is not a business sector to produce educated workers, and is not in the same category as mining industries, trade and services. National education is a govemment effort and all elements of nation to preserve national identity, to transfer norms and values, to sustain and develop the intellectual and cultural base of the society, to give inspiration and pride to citizens, and to promote dialogue for the respect of cultural and social diversity. Some of the main tasks of national education, especially basic and secondary education, is to transfer high values of nation, spirit of nationality, national identity, and to preserve and develop national cultures. These sacred tasks are those of govemment and are the responsibility of nation so that these are impossible to divert to investors of business sector of education services. Liberalization of high education and other sub-sectors of education must be conducted with a strong nationality.